An Option-Theoretic Approach to the Valuation of Dividend Reinvestment and Voluntary Purchase Plans. - Dammon, Robert M; Spatt, Chester S (Journal of Finance, 1992)
Many firms with dividend reinvestment plans also allow their shareholders to voluntarily invest supplemental funds to purchase additional shares. The purchase price for newly issued shares often is determined by the average stock price over a prespecified time period preceding the investment date. This gives the firm's shareholders an option to invest in additional shares only when the stock price exceeds the computed average. This paper uses both theoretical and numerical methods to analyze the value of these voluntary purchase options in theory and practice.